2008
DOI: 10.1186/1471-244x-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with post-traumatic stress disorder and depression amongst internally displaced persons in northern Uganda

Abstract: BackgroundThe 20 year war in northern Uganda between the Lord's Resistance Army and the Ugandan government has resulted in the displacement of up to 2 million people within Uganda. The purpose of the study was to measure rates of post-traumatic stress disorder (PTSD) and depression amongst these internally displaced persons (IDPs), and investigate associated demographic and trauma exposure risk factors.MethodsA cross-sectional multi-staged, random cluster survey with 1210 adult IDPs was conducted in November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
281
11
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(333 citation statements)
references
References 25 publications
36
281
11
5
Order By: Relevance
“…Over 2 million people were displaced into internally displaced people's camps (IDPs) as a consequence of rape, torture, mutilation, destruction of property and many of the people including children were abducted (Roberts et al, 2008;Ovuga et al, 2008). Various studies have shown a high burden of mental disorders (Roberts et al, 2008, Ovuga et al, 2008, Vinck et al, 2007Pfeiffer et al, 2011), ostensibly as a result of civil conflict. For example, Roberts and colleagues reported that 58 % and 67 % of their respondents had posttraumatic stress disorder (PTSD) and depression respectively amongst the internally displaced persons (IDPs).…”
mentioning
confidence: 99%
“…Over 2 million people were displaced into internally displaced people's camps (IDPs) as a consequence of rape, torture, mutilation, destruction of property and many of the people including children were abducted (Roberts et al, 2008;Ovuga et al, 2008). Various studies have shown a high burden of mental disorders (Roberts et al, 2008, Ovuga et al, 2008, Vinck et al, 2007Pfeiffer et al, 2011), ostensibly as a result of civil conflict. For example, Roberts and colleagues reported that 58 % and 67 % of their respondents had posttraumatic stress disorder (PTSD) and depression respectively amongst the internally displaced persons (IDPs).…”
mentioning
confidence: 99%
“…Using the Hopkins Symptom Checklist-25 and the Harvard Trauma Questionnaire, 67% met symptom criteria for depression and 54% for PTSD. 13 More recent data on these conditions, in particular as people have been returning to their homes, are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in mental health responses have been found in populations exposed to multiple types of trauma, including those impacted by displacement and armed conflict. 61,[71][72][73][74][75] Different neural mechanisms in men and women have been proposed to explain these gender disparities. 76,77 In women, higher sensitivity to a corticotropin-releasing factor has been reported, 78 potentially producing higher rates of depression, peritraumatic fear, dissociation, and negative peritraumatic cognitions, in comparison to men's responses.…”
Section: Gendermentioning
confidence: 99%